A Novel pH-Responsive Superabsorbent Hydrogel Based on Collagen for Ephedrine Controlled Release: Hydrogel for Ephedrine Controlled Release - Sadeghia, Mohammad; Hosseinzadeh, Hossein (Biological Sciences - PJSIR, 2013)